Optimizing Blood Pressure Control: A Randomized Comparative Trial of Losartan/Chlorthalidone vs. Losartan/Hydrochlorothiazide - Isabel E. Rucker-Joerg; Ernesto G. Cardona-Muñoz; Francisco G. Padilla-Padilla; Rodrigo Suarez-Otero; Yulia Romero-Antonio; Emmanuel Canales-Vázquez; Kevin F. Rios-Brito; Ileana C. Rodríguez-Vazquez; Jorge González-Canudas (Cardiology and Therapy)
Abstract Introduction Cardiovascular diseases are a leading cause of global mortality, with hypertension as a major risk factor. Low control rates are often attributed to monotherapy, while evidence and clinical guidelines support the effectiveness of combination therapies. This study aimed to evaluate blood pressure changes and the achievement of target levels in patients treated with losartan/chlorthalidone (L/C) compared to losartan/hydrochlorothiazide (L/H). Methods A randomized, double-blind, prospective, multicenter clinical trial was conducted. Patients were assigned to one of two treatment groups, starting with a lower dose (50/12.5 mg of losartan/chlorthalidone or losartan/hydrochlorothiazide). Blood pressure was evaluated at 30 days, and patients not meeting therapeutic goals were escalated to a higher dose (100/50 mg of losartan/chlorthalidone or losartan/hydrochlorothiazide) and followed until the study end (60 days). Results The study recruited 163 patients (83 for losartan/chlorthalidone [L/C] group and 80 for the losartan/hydrochlorothiazide [L/H] group), with a mean age of 53.1 years. Both treatment groups demonstrated significant reductions in systolic and diastolic blood pressure, with L/C achieving an average reduction in systolic blood pressure (SBP) of − 24.6 mmHg and − 13.3 mmHg for diastolic blood pressure (DBP), while L/H had reductions of − 25.3-mmHg and − 11.5 mmHg, respectively. The L/C group exhibited a higher likelihood of achieving blood pressure goals compared to the L/H. Adverse events were comparable between groups and were mostly mild. Conclusions The study showed that both combinations are effective for hypertension, with losartan/chlorthalidone demonstrating greater efficacy in reducing diastolic blood pressure and achieving target levels. Both treatments exhibited similar and favorable safety profiles. Clinical Trials Registration NCT04927299. Registered August 6, 2021- https://clinicaltrials.gov/study/NCT04927299